The Effect of Public Policies on Consumers' Preferences: Lessons from the French Automobile Market - Xavier D'Haultfoeuille; Isis Durrmeyer; Philippe Février (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
In this paper, we investigate whether French consumers have modified their preferences towards environmentally-friendly vehicles between 2003 and 2008. We estimate a model of demand for automobiles incorporating both consumers' heterogeneity and CO2 emissions of the vehicles. Our results show that there has been a shift in preferences towards low-emitting cars, with an average increase of 367 euros of the willingness to pay for a reduction of 10 grams of carbon dioxide per kilometer. We also stress a large heterogeneity in the evolution of preferences between consumers. Rich and young people are more sensitive to environmental issues, and our results are in line with votes for the green party at the presidential elections. We relate these changes with two environmental policies that were introduced at these times, namely the obligation of indicating energy labels by the end of 2005 and a feebate based on CO2 emissions of new vehicles in 2008. Our results suggest that such policies have been efficient tools to shift consumers utility towards environmentally-friendly goods, the shift in preferences accounting for 20% of the overall decrease in average CO2 emissions of new cars on the period.
urn:nbn:de:bvb:19-epub-17262-5
Keywords: D12; H23; L62; Q51; 330; environmental policy; consumers' preferences; CO2 emissions; automobiles